2000
DOI: 10.1359/jbmr.2000.15.4.663
|View full text |Cite
|
Sign up to set email alerts
|

Essential Requirement of BMPs-2/4 for Both Osteoblast and Osteoclast Formation in Murine Bone Marrow Cultures from Adult Mice: Antagonism by Noggin

Abstract: Bone morphogenetic proteins (BMPs) have been heretofore implicated in the induction of osteoblast differentiation from uncommitted progenitors during embryonic skeletogenesis and fracture healing. We have tested the hypothesis that BMPs are also involved in the osteoblastogenesis that takes place in the bone marrow in postnatal life. To do this, we took advantage of the properties of noggin, a recently discovered protein that binds BMP-2 and -4 and blocks their action. Addition of human recombinant noggin to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
127
1
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 302 publications
(135 citation statements)
references
References 35 publications
3
127
1
4
Order By: Relevance
“…Similar to observations by others, we also show moderate to intense expression of BMP2 and BMP7 in bone marrow cells, bone lining cells, osteoblasts, and osteocytes [40,41]. We observed a gradient of BMP7 expression, varying from intense staining at the endosteal side to no staining at the periosteal side of cortical bone.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to observations by others, we also show moderate to intense expression of BMP2 and BMP7 in bone marrow cells, bone lining cells, osteoblasts, and osteocytes [40,41]. We observed a gradient of BMP7 expression, varying from intense staining at the endosteal side to no staining at the periosteal side of cortical bone.…”
Section: Discussionsupporting
confidence: 90%
“…However, the role of BMPs in bone remodeling is not fully understood. BMP2 is produced by bone marrow stromal cells and necessary for osteoblast differentiation [40,41]. Cheng and colleagues [42] reported an osteogenic hierarchy where BMPs 2, 6, and 9 are the most potent agents to induce osteoblast lineagespecific differentiation of mesenchymal progenitor cells, while most BMPs can promote the terminal differentiation of committed osteoblast precursors and osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of inflammation, BMP2 enhances bone resorption via upregulation of COX-2 and RANKL in osteoblasts [92]. In line with this, Noggin , a BMP antagonist, prevents osteoclastogenesis in cultures of the bone marrow [93]. Osteoclasts isolated from long bones, in the presence of RANKL, increased resorption by BMP2 via cathepsin K and carbonic anhydrase II [77].…”
Section: In the Presence Of Coupled Bone Cells Bmps Stimulate Resorptionmentioning
confidence: 84%
“…In contrast, BMP5 and -6 activated osteoclasts in a biphasic mode, depending on the RANKL/ OPG mRNA ratio and the BMP concentration [96]. Mechanistically, BMP2 transcriptionally regulates both RANKL [92,93] and CSF-1 [97], which are critical factors for osteoblastinduced osteoclastogenesis. It is suggested that BMP2 and -7 regulate the osteoclast activity both via OPG-RANKL system and through upregulating the expression of GM-CSF, stromal cell-derived factor-1 (SCF1) and resorption enzymes.…”
Section: In the Presence Of Coupled Bone Cells Bmps Stimulate Resorptionmentioning
confidence: 99%
“…We found the opposite in this study, which suggests that BMP2 may also be involved in regulating periosteal bone resorption. In recent years, studies have in fact found that BMP2 can enhance osteoclastogenesis indirectly by stimulating osteoblasts or stromal cells to produce osteoclast-promoting factors, such as RANKL (Abe et al, 2000;Otsuka et al, 2003), or directly by activating osteoclast differentiation in the presence of RANKL (Jensen et al, 2009). It is hence likely that stronger expression of BMP2 at the anterior periosteal region plays an assisting role in promoting osteoclastogenesis by synergizing with RANKL.…”
Section: Discussionmentioning
confidence: 99%